2021
DOI: 10.1101/2021.04.29.441964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early life stress affects the miRNA cargo in epididymal extracellular vesicles in mouse

Abstract: Sperm RNA can be modified by environmental factors and has been implicated in communicating signals about changes in a father's environment to the offspring. The RNA composition of sperm is influenced during its final stage of maturation in the epididymis by extracellular vesicles released by epididymal cells. We studied the effect of exposure to stress in postnatal life on the transcriptome of epididymal extracellular vesicles using a mouse model of transgenerational transmission. We found that the small RNA … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, one study using a sperm RNA microinjection technique identified miR-375-5p (as well our 15 th differentially expressed miRNA, miR-672-5p) as among the transcripts mediating multigenerational inheritance in a paternal stress exposure model. Our 16 th differentially expressed sperm miRNA, miR-871-3p, was similarly shown to be upregulated in cauda epididymosomes of stress-exposed males [102]. miR-122-5p, as well as the 8 th differentially expressed sperm miRNA, miR-141-3p, were specifically found to regulate Fkbp5 , a glucocorticoid receptor chaperone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, one study using a sperm RNA microinjection technique identified miR-375-5p (as well our 15 th differentially expressed miRNA, miR-672-5p) as among the transcripts mediating multigenerational inheritance in a paternal stress exposure model. Our 16 th differentially expressed sperm miRNA, miR-871-3p, was similarly shown to be upregulated in cauda epididymosomes of stress-exposed males [102]. miR-122-5p, as well as the 8 th differentially expressed sperm miRNA, miR-141-3p, were specifically found to regulate Fkbp5 , a glucocorticoid receptor chaperone.…”
Section: Discussionmentioning
confidence: 98%
“…We previously noted downregulation of basal stress hormones in the F1 generation bred from nicotine-exposed fathers, and our current analysis revealed downregulation of miR-375-3p, miR-672-5p, and miR-871-3p in sperm of mice chronically exposed to nicotine. These miRNAs were found to be up regulated in F0 sperm and cauda epididymosomes in stress-induced multigenerational inheritance models producing heightened stress and depressive phenotypes in rodent offspring [65,102]. Thus, a simple hypothesis supported by these data is that these sperm transcripts act to regulate stress in offspring based on parental experience.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, epigenetic mark ‘A’ is not itself inherited by daughter cells after conception, but rather A affects B affects C until the detectable phenotypic change being measured is produced. Often, the environmental insult producing epigenetic mark A begins in parental somatic cells, not germ cells, and may be long‐lived and able to continuously send signals to germ cells long after the insult has ended (Alshanbayeva et al., 2021; Chan et al., 2020; Duffy et al., 2021; Eaton et al., 2015). While changes in the same detectable epigenetic marks can occur at each stage (A, B, C, etc.)…”
mentioning
confidence: 99%
“…However, additional animal studies are needed to fill current gaps in our understanding of the mechanistic processes underlying germline epigenetic effects. One mechanism the field has converged on involves somatic to germ cell signalling via extracellular vesicles (EVs) (Alshanbayeva et al., 2021; Chan et al., 2020; Chen, Yan, & Duan et al., 2016; Eaton et al., 2015; Franklin et al., 2010; Lambrot et al., 2013; Morgan et al., 2019; Rompala et al., 2018; Spadafora, 2017). For example, rodent models of various paternal environmental stressors have made significant progress in characterizing changes in epididymal EV cargo, including non‐coding RNA and protein content.…”
mentioning
confidence: 99%
“…In addition, recently published research showed that early life stress can affect the microRNAs cargo in epididymal extracellular vesicles, in a mouse model (ALSHANBAYEVA et al, 2021).…”
Section: Discussionmentioning
confidence: 99%